‘We Intend to Move Together in Moving the World’: An Evaluation of the 10th Assembly of the World Council of Churches from 30 October to 8 November 2013 in Busan - Vogelaar, Huub (Exchange, 2016)
The words ‘we intend to move together’ were expressed in the Message of the Assembly of the World Council of Churches (wcc) held in Busan, the second largest city of South Korea. It was a nuanced version of the original phrase of the first Assembly which took place in Amsterdam in 1948 expressing the strong commitment ‘we intend to stay together’. How the 345 member churches of the wcc plan to move together in the upcoming seven years till the next assembly is done in a so-called pilgrimage of justice and peace also communicated in the Message of the Assembly. Below we describe the main characteristics of the vivid 10th assembly, its appealing contexts, as well some of its outcomes. This article will however not comprise the missionary aspects of the assembly. Besides the study of assembly papers my review is also partly a personal account as I took part in the Busan Assembly with a media accreditation.